Reliability of SCIseg Automated Measurement of Midsagittal Tissue Bridges in Spinal Cord Injuries Using an External Dataset. - Connor, J. R.; Thornton, W. A.; Weber, K. A.; Pfyffer, D.; Freund, P.; Tefertiller, C.; Smith, A. C. (Topics in Spinal Cord Injury Rehabilitation)
To determine the interrater reliability between an automated and manual measure of lesion damage following spinal cord injury (SCI) using T2-weighted magnetic resonance images (MRI). Twenty-one MRIs were collected from patients who had completed rehabilitation at Craig Hospital. Manual measurements of midsagittal tissue bridges were conducted by an experienced rater using OsiriX (Pixmeo Sarl, Geneva, Switzerland), and automated measures were taken using the SCIsegV2 automated function through the Spinal Cord Toolbox (SCT). Manual and automated measurements were compared using intraclass correlation coefficients (ICC). Percentage agreement and Cohen's kappa statistic were calculated to compare detection of midsagittal tissue bridges. ICCs between the manual and automated measures were excellent (ICC 0.94, 95% CI 0.84-0.97, P <.001, for ventral tissue bridges; ICC 0.99, 95% CI 0.97-0.99, P <.001, for dorsal tissue bridges). Percentage agreement between raters was 90.8% for ventral, dorsal, and any midsagittal tissue bridge. Cohen's kappa for the detection of tissue bridges showed substantial agreement between the two raters for ventral, dorsal, and any tissue bridges (0.81, P <.001; 0.79, P <.001; and 0.81, P <.001, respectively). Measurements of midsagittal tissue bridges between manual and automated raters are reliable. Automated measurements may help to expedite research related to midsagittal tissue bridges and functional outcomes for individuals with SCI.